(untitled) (mathematica didactica, 2023)
The central place of support for learners with difficulties in mathematics is the regular classroom. Lesson-integrated support starts with the learners’ encounter with the subject matter and focuses on the associated further development of the basic subject matter. The article presents the concept of such a support measure in primary school. To this end, inclusive practices of lesson-integrated support are reconstructed. As a result of interpretative analyses, practices of subject-specific and social participation are characterized, which established in the interaction of the teacher with the pupils.